Effect of high frequency ultrasound pre-treatment on nutritional and technological properties of tomato paste. (March 2022) - Piazza, L; Picchi, V; Cortellino, G; Faoro, F; Masseroni, E; Girotto, F
This study investigates the separate effect of sonication (US, carried out for 5 and 15 min) and thermal treatment (90 °C for 5 min) on nutritional and technological properties of tomato paste. US treatments did not affect the colour parameters and decreased the level of total acidity. Ascorbic acid content was slightly reduced after 5 min US but halved by pasteurization, while total carotenoids (TCC) and lycopene (LC) decreased in non-pasteurized samples after 15 min US. Neither the TCC nor the LC significantly changed in US-pasteurized samples if compared to controls. Microscopic analyses suggested a possible increased bioaccessibility of lycopene in US treated samples due to an enhancement of free lycopene clusters. Viscosity decreased as a consequence of thermal stress, although sonication contributed as well. The present findings suggest that 5 min sonication before pasteurization can enhance the nutritional characteristics of tomato paste, besides improving its texture.